KAJIAN TERHADAP KARAKTERISTIK PERPINDAHAN PANAS PADA LOOP THERMOSYPHON SEBAGAI ALAT RECOVERY PANAS TEMPERATUR RENDAH - Siagian, Parulian; Siahaan, Saloom Hilton; Siagian, Lestina (Jurnal Visi Eksakta, 2020)
The purpose of this study was to examine the effectiveness of the Loop Thermosyphon Heat Exchanger (LTHE) fluidized R134a refrigerant at variations in working fluid pressure of 0.8MPa and 1.2MPa. Thermosyphon is made of three parts, namely, evaporator, condenser and adiabatic part. Evaporators are made of 3/4 inch diameter copper pipe with a length of 3.5 cm. The condenser is made of 3/4 inch diameter copper pipe with a length of 15 cm. The adiabatic part of the steam line is made of copper pipes with a diameter of 3/4 inches and a length of 25 cm and a liquid line with a diameter of 3/8 inches with a length of 27 cm. Things that were investigated included the effect of air flow velocity (heated fluid) of 0.8 m/s, 1m/s, and 1.2m/s on the effectiveness of LTHE and the effect of an increase in evaporator temperature by 400C, 500C, and 600C on the effectiveness of LTHE. The study was conducted experimentally where the LTHE evaporator was heated with a heater. The results of this study show that the effectiveness of LTHE heat transfer work pressure of 1.2 MPa pressure is about 30-68% and higher than the effectiveness of LTHE heat transfer work pressure of 0.8 MPa pressure about 22-35%. Effectiveness decreases with increasing airflow velocity. The LTHE thermal resistance of 0.8 MPa pressure is around 0.3-0.450C/ W and is greater than the LTHE thermal resistance of 1.2 MPa pressure around 0.08-0.40C /W.